2012
DOI: 10.3934/dcds.2012.32.1245
|View full text |Cite
|
Sign up to set email alerts
|

On isotopy and unimodal inverse limit spaces

Abstract: We prove that every self-homeomorphism h : Ks → Ks on the inverse limit space Ks of tent map Ts with slope s ∈ ( √ 2, 2] is isotopic to a power of the shift-homeomorphism σ R : Ks → Ks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…It was proven in [5] by Barge, Bruin and Štimac. As a somewhat surprising by-product of its solution (but in agreement with the results described above), it was shown in [8] that the mapping class group of X is Z. This in turn was used to characterize possible values of the topological entropy of homeomorphisms on these spaces [9].…”
supporting
confidence: 68%
“…It was proven in [5] by Barge, Bruin and Štimac. As a somewhat surprising by-product of its solution (but in agreement with the results described above), it was shown in [8] that the mapping class group of X is Z. This in turn was used to characterize possible values of the topological entropy of homeomorphisms on these spaces [9].…”
supporting
confidence: 68%
“…However, among the p-points there are special ones, which we call salient, which are center points of symmetries in C. Homeomorphisms preserve these symmetries to such an extent that it is possible to prove that salient points map close to salient points. In [10] it was shown that x ∈ K s is a folding point if and only if for some p ∈ N there is a sequence of p-points (x k ) k∈N such that x k → x and L p (x k ) → ∞.…”
Section: Preliminariesmentioning
confidence: 99%
“…Let us denote by ℓ x p a link of C p which contains the point x. From [19] and [2] (for the finite and infinite critical orbit case, respectively) we have the following proposition: From [6,7] and [10] we can derive of the chain C p . Using this notation we can write Proposition 3.1 in the following way: h(x) ≈ p σ R (x) for every x ∈ E q .…”
Section: Construction Of Chains C P and C P+mmentioning
confidence: 99%
See 2 more Smart Citations